Global Data Re-allocation via Communication Aggregation in Chapel - Sanz, Alberto; Asenjo, Rafael; López, Juan; Larrosa, Rafael; Navarro, Angeles; Litvinov, Vassily; Choi, Sung-Eun; Chamberlain, Bradford L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
Chapel is a parallel programming language designed to improve the productivity and ease of use of conventional and parallel computers. This language currently delivers sub optimal performance when executing codes that perform global data re-allocation operations on distributed memory architectures. This is mainly due to data communication that is done without aggregation (one message for each remote array element). In this work, we analyze Chapel's standard Block and Cyclic distribution modules and optimize the communication routines for array assignments by performing aggregation. Thanks to the expressive power of Chapel, the compiler and runtime have enough information to do communication aggregation without user intervention. The runtime relies on the low-level GAS Net networking layer, whose versions of one-sided bulk put/get routines that support strides are particularly useful for us. Experimental results conducted on Hector (a Cray XE6) and Jaguar (Cray XK6)reveal that the implemented techniques can lead to significant reductions in communication time.